Construction of a Novel Female Sterility System for Hybrid Rice - Li, Wei; Guo, Xiaoqiong; Wu, Wenbin; Yu, Weilin; Li, Shichuan; Luo, Di; Wang, Tianjie; Zhu, Qian; Chen, Lijuan; Lee, Dongsun (Frontiers in Plant Science, 2022)
The main constraints of current hybrid rice technology using male sterility (MS) are the low yield and high labor costs of hybrid rice seed (HRS) production. Therefore, there is an urgent need for innovative new hybrid rice technology. Fortunately, we discovered a unique spontaneous sporophytic female-sterile rice mutant controlled by a single recessive locus in the nucleus. Because female-sterile mutant lines cannot produce any selfed-seeds but their pollen has totally normal functions, female sterility (FS) lines may be considered ideal pollen donors to replace the female-fertile pollen donor parent lines currently used in the HRS production. In this study, a genetically engineered FS-based system was constructed to propagate a pure transgene-free FS line using a bentazon herbicide screening. Additionally, the ability of the FS+MS (FM)-line system, with mixed plantings of FS and MS lines, to produce HRS was tested. The pilot field experiment results showed that HRS of the FM-line system were more efficient compared with the conventional FS to MS strip planting control mode. Thus, this study provides new insights into genetic engineering technology and a promising strategy for the utilization of FS in hybrid rice.